Evaluation of The Rate of Microbial Activity in Coconut (Cocos Nucifera L.) Milk When Stored at Different Time Intervals - EBISINTEI, PRECIOUS; Salim, Hotimah Masdan (UNUSA Press, 2024)
Introduction: Coconut milk is a very nutritional milk or drink. The processor of coconut into milk using various forms has been A serious risk and health hazard.Objective: This study aims to describe or evaluate the rate of microbial activity in coconut milk when stored.Methods: The coconut milk was extracted from the coconut meat using an aseptic technique.Results: The initial PH value was 6.10, it was observed that fermentation started from the 12th hour, and at the 24th hour, the PH of the coconut milk was 4.48. After 48 hours, the pH was 4.20 and at the 72nd hour time, the pH value was 3.99. It was also observed that the 24 hours stored coconut milk sample has the highest Bacterial growth rate of 4.12 × 102 and a fungal growth rate of 1.2 × 102.Conclusions: Biochemical test carried out on the bacterial isolate showed Bacillus spp, Staphylococcus aureus, and Bifidobacterium bifidum were observed to be present at 24 hours and 48 hours of the coconut milk sample and at the 72nd hours of the coconut milk sample Pseudomonas spp, Lactobacillus spp, and Aeromonas caviae were observed to be present. A drop of pH value to 3.99 at the 72nd hour was observed due to the activity of Lactobacillus spp